On the Effects of Enforcement on Illegal Markets : Evidence from a Quasi-Experiment in Colombia - Mejía, Daniel (Published by Oxford University Press on behalf of the World Bank, 2018)
This paper studies the effects of enforcement on illegal behavior in the context of a large aerial spraying program designed to curb coca cultivation in Colombia. In 2006, the Colombian government pledged not to spray a 10 km band around the frontier with Ecuador due to diplomatic frictions arising from the possibly negative collateral effects of this policy on the Ecuadorian side of the border. We exploit this variation to estimate the effect of spraying on coca cultivation by regression discontinuity around the 10 km threshold and by conditional differences in differences. Our results suggest that spraying one additional hectare reduces coca cultivation by 0.022 to 0.03 hectares; these effects are too small to make aerial spraying a cost-effective policy for reducing cocaine production in Colombia.